2014
DOI: 10.1109/jsen.2014.2346742
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Sensing Chips With POSFET Array and Integrated Interface Electronics

Abstract: This paper presents the advanced version of novel piezoelectric oxide semiconductor field effect transistor (POSFET) devices-based tactile sensing chip. The new version of the tactile sensing chip presented here comprises of a 4 × 4 array of POSFET touch sensing devices and integrated interface electronics (i.e., multiplexers, high compliance current sinks, and voltage output buffers). The chip also includes four temperature diodes for the measurement of contact temperature. Various components on the chip have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…4 shows the cross section of device. Planar POSFET has been reported by Dahiya et al in past, but due to lack of flexibility, the usage of these tactile sensors are limited to flat areas [3]. In present time there are many post-processing ways and techniques in use which produce thin silicon membrane of thickness ranging from 10 µm -100 µm.…”
Section: Design and Layout Of Bendable Posfetmentioning
confidence: 99%
See 1 more Smart Citation
“…4 shows the cross section of device. Planar POSFET has been reported by Dahiya et al in past, but due to lack of flexibility, the usage of these tactile sensors are limited to flat areas [3]. In present time there are many post-processing ways and techniques in use which produce thin silicon membrane of thickness ranging from 10 µm -100 µm.…”
Section: Design and Layout Of Bendable Posfetmentioning
confidence: 99%
“…Contrary to these, MEMS based approach gives an attractive way to miniaturise and integrate transducer directly in the existing well-developed and fast CMOS technology. One of the promising candidates, Piezoelectric Oxide Semiconductor Field Effect Transistor (POSFET), uses piezoelectric thin film as a transducer on its gate area [3] [4]. However, MEMS based tactile sensing devices cannot withstand large pressure/force due to their inherent fragile nature and therefore lacks flexibility and conformability needed for better integration with curved body parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these materials is limited due to their rigid and brittle nature. Dahiya et al [105] reported development of piezoelectric oxide semiconductor field effect transistors (POSFET) for robotic tactile applications. The device demonstrated a sensitivity of 102.4 mV/N.…”
Section: Smart Structural Engineeringmentioning
confidence: 99%
“…This refers especially on the applied grip force, so as an object to be neither firmly, nor loosely grasped. Solutions that have been explored towards this direction focus on tactile sensing chips that mimic the properties of the human skin [23][24][25][26].…”
Section: Myoelectric Control Systemmentioning
confidence: 99%